Affirmative and silent cyber coverage in traditional insurance policies: Qualitative content analysis of selected insurance products from the German insurance market - Dirk Wrede; Tino Stegen; Johann-Matthias Graf von der Schulenburg (The Geneva Papers on Risk and Insurance - Issues and Practice, 2020)
This paper examines the design of affirmative and silent coverage in view of the cyber risks in traditional insurance policies for select product lines on the German market. Given the novelty and complexity of the topic and the insufficient coverage in the literature, we use two different sources. We analysed the general insurance terms and conditions of different traditional insurance lines using Mayring's qualitative content analysis. Also, we conducted interviews with experts from the German insurance industry to evaluate how insurers understand their silent cyber exposures, and what measures they take to deal with this new exposure. The study shows a considerable cyber liability risk potential for insurers in the considered insurance lines. This arises from the affirmative as well as silent cover inclusions and exclusions for cyber risks, which result from imprecise wordings of insurance clauses and insufficient descriptions of the contractually~specified scope of the insurance coverage.
Keywords: 330; Cyber insurance; Traditional insurance policies; Cyber risk; Silent cyber coverage; Affirmative cyber coverage; Silent cyber